2012
DOI: 10.1016/j.rbmo.2011.10.017
|View full text |Cite
|
Sign up to set email alerts
|

Standardization of catheter load speed during embryo transfer: comparison of manual and pump-regulated embryo transfer

Abstract: The position of transfer air bubbles after embryo transfer is related to the pregnancy rate. With the conventional manual embryo-transfer technique it is not possible to predict the final position of the air bubbles. This position mainly depends on the catheter load speed at transfer (injection speed), a parameter that remains uncontrollable with the conventional technique even after standardization of the protocol. Therefore, the development of an automated device that generates a standardized injection speed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 15 publications
1
12
0
Order By: Relevance
“…• Operator experience (Groeneveld et al, 2012;Kably Ambe et al, 2011;Karande et al, 1999;Lu et al, 1999;Hearns-Stokes et al, 2000;Yao et al, 2009). …”
Section: Introductionmentioning
confidence: 99%
“…• Operator experience (Groeneveld et al, 2012;Kably Ambe et al, 2011;Karande et al, 1999;Lu et al, 1999;Hearns-Stokes et al, 2000;Yao et al, 2009). …”
Section: Introductionmentioning
confidence: 99%
“…1). This device enables a better controlled positioning of the embryo(s) inside the uterine cavity, extensively described by Groeneveld et al [25]. The results of this in vitro study strongly indicated that the PRET device generates a reliable and reproducible injection speed and pressure and, therefore, brings new possibilities for further standardization and potential optimization of the embryo transfer procedure, compared to the manually performed embryo transfer.…”
Section: Introductionmentioning
confidence: 52%
“…In a manually performed embryo transfer, the inner catheter was loaded and unloaded by the laboratory technician using a simple syringe; in a PRET, the syringe was replaced by the PRET device. The PRET device is developed to perform the embryo transfer in a standardized and reproducible way; the technical aspects of the PRET device were previously described by Groeneveld et al [25]. The inner catheter is connected to the PRET device and loaded by the laboratory technician using the device's scroll-wheel interface.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations